3D model of intra-yarn fiber volume fraction gradients of woven fabrics. (15th November 2017) - Mühlstädt, Mike; Seifert, Wolfgang; Arras, Matthias M.L.; Maenz, Stefan; Jandt, Klaus D.; Bossert, Jörg
Abstract: Accurate predictions of laminate strength is important for engineering. Overestimations of laminate strength can be due to variations in local fiber volume fraction. However, intra-yarn fiber volume fraction gradients ( G ) within laminated plain woven fabrics (PWF) have not been investigated sufficiently to consider their effect in laminated strength predictions. This study addresses this shortening by a proper determination of G in laminated PWFs and proposes a corresponding model (GM). We tested the hypothesis that G can be modeled according to analytical models of the laminates meso-level structure. All required parameters were determined from scanning electron microscopy images of laminated PWFs of different fiber volume fraction. The GM was implemented in Matlab and matches the experimental data well. In addition, finite element simulation of interlaced yarns were conducted to understand the origin of G . The proposed model is a 3D description of G in PWFs. Using this model may lead to a significantly improved prediction of the laminate strength.